PERCEPTION DE LA RETRAITE ET REPRESENTATION SOCIALE DU TRAVAIL CHEZ LES EMPLOYES PROCHES DE LA RETRAITE : CAS DES EMPLOYES D’UNE ENTREPRISE AGRO-INDUSTRIELLE DU SUD-OUEST DE LA COTE D’IVOIRE, LA SOGB (SOCIETE DE CAOUTCHOUC DE GRAND-BEREBY) - N’da Lazare, Koua (European Scientific Journal, ESJ, 2012)
This study deals with the problem of retire perception and workers’ social representation of work at the approach of the phenomenon of retire. We have notice in the first way that employers who have made socio-economical realization during their professional curriculum have positive social representation of work than the others who have made no socio-economical realization. Secondly, we notice that, more the employers have positive perception of retire more they have negative social representation of work. Socio-professional category can also be observed as a parameter of retire perception; in fact we notice that executives and supervisors have a more positive perception of retire than sample employers. We can also notice that the employers who have post-professional projects have more positive perception of retire than them who have no post-professional projects. At least, stress at the evocation of retire could be justified by economical and social psychological reasons in all socio-professional categories.